Reading the Entanglements of Nature-culture Conservation and Development in Contemporary India. (April 2021) - Rajangam, Krupa; Sundar, Aparna
In this article we argue for greater attention to the practice of (nature-culture) conservation as a specific form of intervention with implications for development. Outlining the dominant frameworks through which the often vexed relationship between conservation and development has been understood, the article offers an alternative analytical framework that is grounded in ethnographic attention to everyday practice. Applying this framework, the three papers in this special section examine conservation-development dilemmas at diverse conservation sites in India—Rushikulya, Orissa, a globally significant site for the conservation of marine turtles; Nagarahole, in southern Karnataka, one of India's most successful tiger reserves; and the Hampi region, northern Karnataka, where the archaeological remains of the medieval Vijayanagara Empire have been designated a UNESCO World Heritage Site (WHS). The papers reveal a relationship between conservation and development that is paradoxically both more structurally imbricated and more contingent and variable than a focus on official frameworks, discourses and plans would suggest. They lead us to argue that, rather than focusing on the stated objectives of the formal conservation plan alone, attention to its ambivalent adoptions and unintended outcomes, as well as to negotiations between diverse actors and forms of knowledge, can contribute to both a more balanced theorization of conservation's relation to development as well as to more effective conservation practices.